Developing technical thinking of students in the process of preparation for professional activity - Ismailova Z.; Ashurova S.; Nasimova Z.; Sultanov A.; Shukurova O.; Norqobilov M. (BIO Web of Conferences, 2023)
The article analyzes the scientific ideas of technical thinking and determines its role and importance in the professional activity of the engineer, analyzes the state of the problem of developing students’ technical thinking in psychological and pedagogical theory and practice in higher education, specializes in the development of technical thinking generalization and systematization in accordance with the quality characteristics, as well as the development of technical thinking of engineering students and the development of a mechanism for its implementation.